Kallikrein-related peptidases (KLKs) in gastrointestinal cancer: Mechanistic and clinical aspects - Kontos, Christos K.; Mavridis, Konstantinos; Talieri, Maroulio; Scorilas, Andreas (Thrombosis and Haemostasis, 2013)
The human tissue kallikrein (KLK1) and kallikrein-related peptidases (KLKs) are secreted serine proteases with diverse expression patterns and physiological roles in different systems, including the digestive system. The aberrant expression of KLKs in gastrointestinal malignancies as well as their implication in carcinogenesis including cell growth regulation, angiogenesis, invasion, and metastasis, has prompted scientists to investigate their potential as cancer biomarkers. Expression of distinct KLKs is associated with various clinic-pathological parameters of patients with gastric, colorectal, pancreatic, hepatic, and esophageal cancer. Moreover, several KLKs possess significant favourable or unfavourable prognostic value in these human malignancies. Identification of novel diagnostic, prognostic and predictive biomarkers will contribute utmost to clinical decision-making, since early diagnosis of gastrointestinal cancer and early detection of recurrence following surgery are critical for the effective treatment of patients and for a positive clinical outcome. The current review provides a brief overview of the functional role of KLKs in gastric, colorectal, pancreatic, hepatic, and esophageal cancer, and describes the current status of KLKs as potential tumour biomarkers in these human malignancies.
Keywords: Gastric cancer; colorectal cancer; pancreatic carcinoma; molecular tumour markers; kallikrein splice variants